The lamellar spacing in self-assembling bacteriochlorophyll aggregates is proportional to the length of the esterifying alcohol - Psencík, Jakub; Torkkeli, Mika; Zupcanová, Anita; Vácha, Frantisek; Serimaa, Ritva E; Tuma, Roman (Photosynthesis research, 2010)
Chlorosomes from green photosynthetic bacteria are large photosynthetic antennae containing self-assembling aggregates of bacteriochlorophyll c, d, or e. The pigments within chlorosomes are organized in curved lamellar structures. Aggregates with similar optical properties can be prepared in vitro, both in polar as well as non-polar solvents. In order to gain insight into their structure we examined hexane-induced aggregates of purified bacteriochlorophyll c by X-ray scattering. The bacteriochlorophyll c aggregates exhibit scattering features that are virtually identical to those of native chlorosomes demonstrating that the self-assembly of these pigments is fully encoded in their chemical structure. Thus, the hexane-induced aggregates constitute an excellent model to study the effects of chemical structure on assembly. Using bacteriochlorophyllides transesterified with different alcohols we have established a linear relationship between the esterifying alcohol length and the lamellar spacing. The results provide a structural basis for lamellar spacing variability observed for native chlorosomes from different species. A plausible physiological role of this variability is discussed. The X-ray scattering also confirmed the assignments of peaks, which arise from the crystalline baseplate in the native chlorosomes.
Keywords: hexany; kvarterní struktura proteinů; Anisotropy; Chlorobium; Esterification; bakteriochlorofyly; Hexanes; X-Rays; Protein Structure, Quaternary; anizotropie; rentgenové záření; Scattering, Radiation; radiační rozptyl; esterifikace; alkoholy; Cellular Structures; buněčné struktury; Bacteriochlorophylls; Alcohols